PENGEMBANGAN MEDIA PEMBELAJARAN ULAR TANGGA KEANEKARAGAMAN HAYATI (ULTAKA) UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS VII MTs NEGERI 2 KOTA KEDIRI - Auliyaur Rohmah, Sayyidah; Wenie Ananda Pramudiea Margarieta (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The urgency of this research arises from the need to address the low learning motivation in science (IPA) among Grade VII F students at MTs Negeri 2 Kota Kediri. By developing a learning media called UTAKA (Ular Tangga Keanekaragaman Hayati or Biodiversity Snakes and Ladders), it is expected that a more engaging, interactive, and contextual learning atmosphere can be created, thereby enhancing students’ motivation and understanding of science material. This research is also intended to serve as a reference for the development of innovative instructional media in other schools, particularly in efforts to integrate biodiversity values into the learning process. Based on this background, the purpose of this study is stated in the title: